Shear strengthening of plate girders using carbon-fibre-reinforced polymer composites. Issue 2 (11th April 2021) - Azizi, Saeed; Mehmandoost Kotlar, Hossein; Narmashiri, Kambiz
Abstract : New methods for strengthening steel structures using fibre-reinforced polymer composites have been the subject of much recent research. Few studies have been carried out on shear strengthening of plate girders using carbon-fibre composites. In the study reported in this paper, the impact of carbon-fibre composite plates on end-zone shear capacity of steel-plate girders is investigated. A section of plate girder with a length and height of 300 mm was chosen for numerical modelling. All specimens were modelled using finite-element software. Initially, the software was verified using experimental data available in the literature. Eleven specimens with different arrangements of composite strips on the web of the plate girders were then investigated. Different ratios of composites were pasted on one side or both sides of the web. Static non-linear methods were used to analyse the specimens. The results indicated that fully strengthening the plate girders on both sides of the web significantly increased bearing capacity.